2018
DOI: 10.1055/s-0038-1642037
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulable States and Thrombophilias: Risks Relating to Recurrent Venous Thromboembolism

Abstract: Inherited and acquired thrombophilias and hypercoagulable states, such as active cancer, estrogen-induced, autoimmune disorders, major surgery, hospitalization, and trauma, are well-known risk factors for venous thromboembolism (VTE). The effect of these on recurrent VTE is different for each specific risk factor. The major risk factors affecting VTE recurrence include the presence of active cancer and an unprovoked first VTE. In addition, the use of combined female hormones in a woman with a previous history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“… 10 Acquired thrombophilia includes antiphospholipid syndrome (APS), among other autoimmune disorders such as Behcet's disease. 11 The primary instance in which testing for thrombophilia leads to a change in treatment is the presence of APS, for which warfarin is recommended rather than a direct oral anticoagulant (DOAC). 12 The presence of APS is furthermore distinguished from the significant determination of provoked versus unprovoked VTEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Acquired thrombophilia includes antiphospholipid syndrome (APS), among other autoimmune disorders such as Behcet's disease. 11 The primary instance in which testing for thrombophilia leads to a change in treatment is the presence of APS, for which warfarin is recommended rather than a direct oral anticoagulant (DOAC). 12 The presence of APS is furthermore distinguished from the significant determination of provoked versus unprovoked VTEs.…”
Section: Discussionmentioning
confidence: 99%
“…There are differing opinions regarding anticoagulation and thrombophilia, since the literature is unclear if they confer a higher risk of recurrence. 11 Some, such as Stevens et al, recommended not performing thrombophilia testing following an episode of provoked VTE, as a positive test is not enough to determine the duration of anticoagulation and may subject patients to otherwise avoidable bleeding risks. 8 They also reported that thrombophilia testing should not be performed in patients after a single episode of unprovoked VTE because a negative result is not enough to stop anticoagulation in a patient with low bleeding risk and willingness to continue therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of influence of inherited thrombophilia on the risk of VTE recurrence remains controversial[ 10 ]. In our cohort, stent patency and re-intervention rates were not significantly different between thrombophilia positive and negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma patients with thrombosis need not be routinely examined for hereditary thrombophilia [ 61 ]. In contrast, thrombotic events are 2–20 times more likely to occur in trauma patients with other types of thrombophilia [ 62 ], so thrombophilia testing is recommended for patients with recurrent post-traumatic thromboembolism or family history of thrombotic disease [ 63 ] (Table 1 ).…”
Section: Pathophysiological Mechanismmentioning
confidence: 99%